Arsenate and antimonate adsorption competition on 6-line ferrihydrite monitored by infrared spectroscopy. (October 2015) - Muller, Tim; Craw, Dave; McQuillan, A. James
Graphical abstract: Highlights: Arsenate and antimonate adsorption competition on 6-line ferrihydrite. Adsorption kinetics and adsorbed species revealed by infrared (IR) spectroscopy. IR absorptions give relative surface concentrations with batch adsorption studies. Adsorption affinities similar in acid media but antimonate weaker in neutral media. Environmental concern from weak antimonate adsorption to HFO in neutral media. Abstract: Arsenate and antimonate are water-soluble toxic mining waste species which often occur together and can be sequestered with varying success by a hydrous ferric oxide known as ferrihydrite. The competitive adsorption of arsenate and antimonate to thin films of 6-line ferrihydrite has been investigated using primarily adsorption/desorption kinetics monitored by in situ attenuated total reflectance infrared (ATR-IR) spectroscopy on flowed solutions containing 10 −3 and 10 −5 mol L −1 of both species at pH 3, 5, and 7. ICP-MS analysis of arsenate and antimonate adsorbed to 6-line ferrihydrite from 10 −3 mol L −1 mixtures in batch adsorption experiments at pH 3 and 7 was carried out to calibrate the relative surface concentrations giving rise to the IR spectral absorptions. The kinetic data from 10 −3 and 10 −5 mol L −1 mixtures showed that at pH 3 antimonate achieved a greater surface concentration than arsenate after 60 min adsorption on 6-line ferrihydrite. However, at pH 7, the adsorbed arsenate surface concentration remained relatively high while that of adsorbed antimonate was much reduced compared with pH 3 conditions. Both species desorbed slowly into pH 3 solution while at pH 7 most adsorbed arsenate showed little desorption and adsorbed antimonate concentration was too low to register its desorption behaviour. The nature of arsenate which is almost irreversibly adsorbed to 6-line ferrihydrite remains to be clarified.